¿Royalties Para Los Periodistas? Periodismo Y Propiedad Intelectual En La Nueva Legislación Española - Velasco Quintana, Pablo (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
News, articles, and all genres of journalism can generate copyrights, and are in the area of copyright laws. This text studies the fact of the called "clipping press” and the answer of the new Spanish copyright law.